Raising a Bilingual Child: Nurturing First Language Oral Skills at Home (2016)
From my experience as a mother trying to raise a bilingual child and the professional experience as an ESL preschool teacher, I found interesting to describe the development of oral language skills and communicative abilities of Spanish as the Mother Tongue (MT) in a girl who is in the process of becoming bilingual in particular context where she is immerse in a monolingual environment by attending the English Speakers of Other Languages (ESOL) program. This study will document a specific strategy I have implemented during the last year providing support to the minority language by giving quality of exposure to the First Language (L1). This research is to be used with ESL students, parents and educators of ESOL classrooms. The population to be analyzed is my own daughter, Laura, who is enrolled in the ESOL program and denied the Bilingual program after being diagnosed ELP (English Limited Proficiency) at the age of 4. As a personal fact it started when my daughter was about to begin preschool and I had to decide whether she was attending a Dual Language (DL) or an ESOL program. At first I made some research about the Dual Language programs and I found out that the DL program is only for elementary and that for middle and high school there is only English instruction. Having discovered this, I decided for my daughter to attend the ESOL program so she could have better foundations in English by being fluent and literate in English from the beginning of her school life. As important as this, my desire for her is to be Bilingual due to all the benefits that it involves. For this reason, I wanted to take care of our Tongue Language (TL), Spanish as well.